Birds as Landscape Elements in Urban Parks: A Comparative Study on the Perception between Indonesian and Japanese People - Sry Wahyuni; Katsunori Furuya (Indonesian Journal of Environment and Sustainable Development, 2017)
Birds are both a landscape element and a common form of wildlife found in urban parks. Human’s perceptions of their surrounding landscapes need to be understood in order to create better environments. This study aimed to determine and evaluate the aesthetic quality of landscapes regarding birds as landscape elements, and to compare the results between Indonesian and Japanese people. The data were analyzed using scenic beauty estimation, the Mann-Whitney U Test, and the Spearman Correlation. A total of 252 respondents evaluated landscape images and answered a questionnaire. The results showed that landscape images with birds were given lower scenic beauty scores from Japanese respondents than they were from Indonesian respondents. There were significant differences between Indonesian and Japanese respondents in four landscape images with birds and two landscape images with human-bird interactions. Besides this, there were different strengths in correlations between landscape images with and without birds and landscape images with and without human-bird interactions among Indonesian and Japanese respondents. In conclusion, the existence of birds as landscape elements in urban parks had an influence on the perceptions and preferences of Indonesian and Japanese respondents. However, there was a difference in how they appreciated birds as landscape elements.Keywords: cross-cultural, landscape images, preference, scenic beauty estimation, urban wildlife